Panama : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper assesses the effectiveness of Panama's fiscal framework. The fiscal framework of Panama has played an important role in enhancing fiscal discipline since its establishment in 2009. Since the current fiscal framework went into effect in 2009, the primary balance and debt-to-GDP ratio of the nonfinancial public sector have improved significantly on average compared with those in 2000-08. The fiscal impulse given the output gap also shows that fiscal policy was less procyclical in 2009-15 than in 2001-08. However, there are options to better align the framework with best practice, including reducing unintended procyclicality, increasing transparency, and improving accountability.